Cryptic diversity and female host specificity in a parasitoid where the sexes utilize hosts from separate orders. - Hayward, A; McMahon, D; Kathirithamby, J (2011)
Investigating complex parasitic life cycles is important for understanding the major fitness components that drive the evolution of host-parasite systems. The rare condition of heterotrophic heteronomy, in which the sexes utilize disparate host taxa, is a poorly understood complex parasitic lifestyle. One of only two known examples occurs in the Myrmecolacidae, an unusual family of the parasitoid order Strepsiptera (Insecta), in which males parasitize ants while females parasitize grasshoppers, crickets, and praying mantids. Here, we reconstruct the evolutionary pattern and timescale of host-use in a set of morphologically cryptic myrmecolacid taxa currently identified as Caenocholax fenyesi. We find that (i) C. fenyesi contains at least ten cryptic lineages consistent with separate species; (ii) Fossil evidence suggests a very low molecular clock rate and an ancient origin for cryptic lineages; (iii) Diversity among Caenocholax species is partitioned by geography and host association of the female; and (iv) Switches in host usage are uncoupled between the sexes, with changes in female host preference accompanying diversification. This study represents the first phylogeographical analysis of any strepsipteran, and the first molecular examination of host-use for a heterotrophic heteronomous taxon. Our results have implications for the understanding of evolution, host usage and estimated species richness in parasitic taxa.